HAPTIC VISUALIZATION USING VISUAL TEXTURE INFORMATION - Adi, Waskito (2011)
Haptic enables users to interact and manipulate virtual objects. Although haptic research has influenced many areas yet the inclusion of computer haptic into computer vision, especially content based image retrieval (CBIR), is still few and limited. The purpose of this research is to design and validate a haptic texture search framework that will allow texture retrieval to be done not just visually but also haptically. Hence, this research is addressing the gap between the computer haptic and CBIR fields. In this research, the focus is on cloth textures. The design of the proposed framework involves haptic texture rendering algorithm and query algorithm. The proposed framework integrates computer haptic and content based image retrieval (CBIR) where haptic texture rendering is performed based on extracted cloth data. For the query purposes, the data are characterized and the texture similarity is calculated. Wavelet decomposition is utilized to extract data information from texture data. In searching process, the data are retrieved based on data distribution. The experiments to validate the framework have shown that haptic texture rendering can be performed by employing techniques that involve either a simple waveform or visual texture information. While rendering process was performed instability forces were generated during the rendering process was due to the limitation of the device. In the query process, accuracy is determined by the number of feature vector elements, data extraction, and similarity measurement algorithm. A user testing to validate the framework shows that users’ perception of haptic feedback differs depending on the different type of rendering algorithm. A simple rendering algorithm, i.e. sine wave, produces a more stable force feedback, yet lacks surface details compared to the visual texture information approach.